Specific Staining of Muscle Cytoskeletal Proteins in Litopenaeus vannamei and Their Role in Textural Deterioration during Refrigeration - CAI Peifeng, LIAO Weilong, FENG Jun, HU Li, LI Caihong, XU Defeng (Shipin Kexue)
To clarify the key material basis for the rapid softening of shrimp muscle during refrigeration, this study established a specific histological detection method for cytoskeletal proteins and analyzed the correlation between the degradation of cytoskeletal proteins and texture deterioration. By comparing the effects of different fixatives, dehydration modes, clarification times, and staining parameters on the staining of cytoskeletal proteins, it was found that the suitable fixative solution for shrimp muscle tissue was Carnoy’s fixative; the specific staining process encompassed five steps: 1) 15 h fixation at room temperature, 2) dehydration with a series of gradient ethanol concentrations, 3) sequential clarification with a mixture of xylene and ethanol followed by xylene, 4) paraffin embedding for sectioning, 5) and Masson’s trichrome staining, clearly showing the morphology of nuclei, myofibrils, and collagen fibers. The pathological results showed that the gap between muscle fiber bundles increased with refrigeration time, and the structure of myofibrillar bundles was partially destroyed. The color of stained collagen fibers became gradually lighter indicating a decrease in its amount. Quantitative analysis showed that refrigeration led to a significant decrease in the volume fraction of collagen fibers and myofibrils in muscle tissue (P < 0.05). The volume fraction of myofibrils in cross-section and longitudinal sections decreased from (91.03 ± 1.37)% and (93.39 ± 0.91)% to (41.14 ± 3.78)% and (24.36 ± 3.67)%, respectively, over a 5-day refrigeration period. The cross-sectional and longitudinal areas of shrimp myofibrils and collagen fibers were significantly positively correlated with muscle hardness and elasticity (P < 0.05), indicating that the reduction in myofibril and collagen contents during refrigeration was closely related to texture deterioration. The significant correlation between the structural degradation of cytoskeletal proteins and texture deterioration revealed their key role in texture preservation and was an important target for early monitoring and intervention of muscle softening.